2012
DOI: 10.1021/jf300890d
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Galacto-oligosaccharides in an Organic–Aqueous Biphasic System by a Novel β-Galactosidase from a Metagenomic Library

Abstract: Prebiotic galacto-oligosaccharides (GOS) were effectively synthesized from lactose in organic-aqueous biphasic media by a novel metagenome-derived β-galactosidase BgaP412. A maximum GOS yield of 46.6% (w/w) was achieved with 75.4% lactose conversion rate in the cyclohexane/buffer system [95:5 (v/v) cyclohexane/buffer] under the optimum reaction conditions (initial lactose concentration = 30% (w/v), T = 50 °C, pH 7.0, and t = 8 h). The corresponding productivity of GOS was approximately 17.5 g L(-1) h(-1). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
2
12
2
Order By: Relevance
“…In contrast to this, several authors have reported maximum GOS at high (30-40%) lactose concentration [7,23,24,32]. This was attributed to high availability of both the donor and the acceptor molecules for transgalactosylation, suppression of water activity thereby reducing hydrolysis [24]. In the present study, the b-galactosidase produced by the selected yeast performed well at lower lactose concentration producing significant amount of GOS as compared to other studies.…”
Section: Effect Of Initial Lactose Concentration On Gos Synthesiscontrasting
confidence: 85%
See 4 more Smart Citations
“…In contrast to this, several authors have reported maximum GOS at high (30-40%) lactose concentration [7,23,24,32]. This was attributed to high availability of both the donor and the acceptor molecules for transgalactosylation, suppression of water activity thereby reducing hydrolysis [24]. In the present study, the b-galactosidase produced by the selected yeast performed well at lower lactose concentration producing significant amount of GOS as compared to other studies.…”
Section: Effect Of Initial Lactose Concentration On Gos Synthesiscontrasting
confidence: 85%
“…These results were supported by the b-galactosidase of B. longum where maximum GOS yield was observed at 6.8 [7]. Similar observations of high GOS yield at pH 7.0 were observed for a b-galactosidase derived from a metagenomic library [24]. In general, b-galactosidase from yeast or bacterial origin have more neutral pH optima between 6.0 and 7.5, while b-galactosidases from filamentous fungus, such as A. oryzae, show maximum GOS formation at low pH [24].…”
Section: Effect Of Initial Lactose Concentration On Gos Synthesissupporting
confidence: 75%
See 3 more Smart Citations